2023
DOI: 10.1186/s12889-023-16562-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of healthcare workers' knowledge and attitude on Ebola virus disease in Somalia: a multicenter nationwide survey

Abdirahman Khalif Mohamud,
Ikran Abdulkadir Ali,
Ahmed Isse Ali
et al.

Abstract: Background In September 2022, a new Ebola outbreak was reported in Uganda, East Africa, and 142 confirmed cases, including 19 Healthcare workers (HCWs) reported. Ebola is not endemic in Somalia, but the country is at a reasonable risk of the virus being introduced due to the direct connection with daily flights from Uganda without border health control and prevention activities. Therefore, evaluating HCWs' Knowledge and attitude is crucial since this is the first time being evaluated in Somalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…This study revealed that the likelihood of HBV infection is higher among low-income and jobless blood donors compared to their counterparts. Generally, poverty and infectious diseases are interlinked, particularly HBV infection due to lower socioeconomic status often associated with poorer living habits [ 49 , 50 ]. For instance, sharing personal items like razors or nail clippers among individuals in poverty may increase the risk of infection, as HBV can survive outside of the body for at least seven days [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the likelihood of HBV infection is higher among low-income and jobless blood donors compared to their counterparts. Generally, poverty and infectious diseases are interlinked, particularly HBV infection due to lower socioeconomic status often associated with poorer living habits [ 49 , 50 ]. For instance, sharing personal items like razors or nail clippers among individuals in poverty may increase the risk of infection, as HBV can survive outside of the body for at least seven days [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the attitude section used a scoring system ranging from strongly disagree (1 score) to strongly agree (5 score) or vice versa for negative statements with a maximum score of 60. Responses were categorized as negative attitude (< 60%), neutral attitude (60-79%), and positive attitude (≥ 80%) based on Bloom's cut-off point classi cation [28][29][30][31]. The practice section scored "1" for correct responses (always) and "0" for incorrect responses (never and occasionally), with a maximum expected score of 10.…”
Section: Research Instruments and Measurementsmentioning
confidence: 99%
“…The practice section scored "1" for correct responses (always) and "0" for incorrect responses (never and occasionally), with a maximum expected score of 10. Categories were designated as poor practice (< 60%), moderate practice (60-79%), and good practice (≥ 80%) based on Bloom's cutoff point classi cation [26][27][28][29][30][31].…”
Section: Research Instruments and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations